A three step protocol for the development of an innovative footwear (shoe and sensor based insole) to prevent diabetic foot ulceration - Sousa, Liliana B.; Almeida, Inês; Bernardes, Rafael A.; Leite, Teófilo R.; Negrão, Rui; Apóstolo, João; Salgueiro-Oliveira, Anabela; Parreira, Pedro (Frontiers in Public Health, 2023)
Background The incidence of diabetic foot ulceration (DFU) is increasing worldwide. Therapeutic footwear is usually recommended in clinical practice for preventing foot ulcers in persons with diabetes. The project Science DiabetICC Footwear aims to develop innovative footwear to prevent DFU, specifically a shoe and sensor-based insole, which will allow for monitoring pressure, temperature, and humidity parameters. Method This study presents a three-step protocol for the development and evaluation of this therapeutic footwear, specifically: (i) a first observational study will specify the user requirements and contexts of use; (ii) after the design solutions were developed for shoe and insole, the semi-functional prototypes will be evaluated against the initial requirements; (iii) and a pre-clinical study protocol will enable the evaluation of the final functional prototype. The eligible diabetic participants will be involved in each stage of product development. The data will be collected using interviews, clinical evaluation of the foot, 3D foot parameters and plantar pressure evaluation. This three-step protocol was defined according to the national and international legal requirements, ISO norms for medical devices development, and was also reviewed and approved by the Ethics Committee of the Health Sciences Research Unit: Nursing (UICISA: E) of the Nursing School of Coimbra (ESEnfC). Results The involvement of end-users (diabetic patients) will enable the definition of user requirements and contexts of use to develop design solutions for the footwear. Those design solutions will be prototyped and evaluated by end-users to achieve the final design for therapeutic footwear. The final functional prototype will be evaluated in pre-clinical studies to ensure that the footwear meets all the requirements to move forward to clinical studies. Discussion The three-step study outlined in this protocol will provide the necessary insights during the product development, ensuring this new therapeutic footwear's main functional and ergonomic features for DFU prevention.